The importance of incorporating the undercover agent in the Ecuadorian Legislation - Proaño Reyes, Gladis (Iuris Dictio, 2018)
Settling criminal acts to uncover another crime shall be reason for investigation. In these circumstances, the basic principles of law, specialty, subsidies, proportion, jurisdictional control and legal security will need to be justified before infiltrating an undercover agent in an organized crime entity that uses cyberspace. Technology is replacing the participation of undercover agents, as technical devices allow an invisible way to observe and be present, scan, describe, listen and collect information from a potential crime scene, regardless of geographical limits and borders. This is particularly important when global crimes require international cooperation and mutual assistance between countries to deal with cyberspace that need the intervention of a cyber undercover agent.